Critical Narrative of Santri Against Fake News and Religious Moderation - Zulyadi, Teuku; Akmal, Saiful; Putri, Nanda; Maulida, Titin Arifa; Fazri, Anhar (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
In the era of disruption, digital literacy is a must in the communication process, particularly for students or santri in schools and madrassas. As one of the most active social media users, Madrasah and Dayah students must understand the difference between trustworthy and fake news (hoaxes) that has been mixed in cyberspace, susceptible news that has the potential to affect the realm of law and religious extremism. The digital literacy assistance targets Aliyah students in four popular boarding schools in Banda Aceh and Aceh Besar regency, with a focus on debunking fake news. This paper employs participatory learning and action (PLA) as a technique for assisting school-aged children. In practice, it was discovered that Aliyah students have a limited understanding of digital literacy, particularly in relation to factors that contribute to the suppression of fake news. It is anticipated that the results make a significant contribution to socialization efforts and targeted campaigns to raise awareness of digital literacy among elementary and secondary school-aged children, as well as its incorporation into the curriculum.